Review of the buccal-attaching fish parasite genus Glossobius Schioedte & Meinert, 1883 (Crustacea: Isopoda: Cymothoidae) - Martin, Melissa B.; Bruce, Niel L.; Nowak, Barbara F. (Zootaxa, 2015)
Two species of Glossobius Schioedte & Meinert, 1883 are known from Australia: Glossobius anctus Bruce & Bowman, 1989 and Glossobius impressus (Say, 1818), the latter recorded here for the first time from Australia and southern Africa. Glossobius ogasawarensis Nunomura, 1994 is here placed in synonymy with Glossobius auritus Bovallius, 1885; whereas Glossobius crassa (Dana, 1853) is removed from synonymy with G. auritus and placed into nomen dubium. Glossobius arimae Nunomura, 2001 is transferred to the genus Ceratothoa Dana, 1852. A key to the species of Glossobius is presented.